MYC Gene Mutations as Causative Pathways for Development and Treatment of Hematological Malignancies - Saeed M Kabrah (Indian Journal of Forensic Medicine & Toxicology, 2022)
MYC is a proto-oncogene with deregulation of >50% of human cancers. The dysregulation of MYC causetumorigenesis, cell growth and proliferation, cell growth, and apoptosis. Novel therapy approaches leadto the direct inhibition of the MYC gene by disruption of MYC/Max complex, MYC destabilization,inhibition of MYC translation and/or transcription. Cetuximab and panitumumab act on the epidermalgrowth factor receptor (EGFR). Cetuximab is an immunoglobin G1 isotype of a monoclonal antibodythat produces antibody-dependent cell-mediated. Panitumumab is an immunoglobulin G2 isotypemonoclonal antibody. This antibody acts on different site of EGFR with different degree of affinity.Genome-wide association studies e.g., TWAS determine the aggregate genotypes. Enhancer is cellspecificgene regulation that cluster for binding sites of a transcription factor with spatially coordinatedto control the expression of one or more specific target genes. In this review, we will summarize noveldrugs in targeting cancerous MYC in haematological malignancy.